A novel vehicle communication paradigm based on Cellular Networks for improving the safety in roads. (15th May 2008) - Santa, Jose; Toledo-Moreo, Rafael; Gomez-Skarmeta, Antonio F.
Main aim of Intelligent Transport Systems (ITS) applied to roads is to increase their safety. To achieve this goal, many researchers are focused on developing robust and efficient communication links between vehicle to infrastructure (V2I) and Vehicle to Vehicle (V2V). Most of the works in the current literature are based on vehicular ad hoc networks. This paper presents a network infrastructure based on Cellular Networks (CNs) and Peer to Peer (P2P) technologies, to develop a communication paradigm for improving road safety, and integrating both V2I and V2V in one design. For localisation purposes, a Global Navigation Satellite Systems (GNSS) is used. Since we are dealing with safety applications, a very special emphasis on the integrity of the positioning is put, and an integrity parameter which measures it is used to improve the location of road incidences. Details of the prototype developed and the tests performed in a real environment are given.